A semi-analytical solution of micro polar flow in a porous channel with mass injection by using differential transform method - Rashidi, M. M. M.; Pour, S. A. Mohimanian Mohimanian; Laraqi, N. (Nonlinear Analysis: Modelling and Control, 2010)
In this letter, the differential transform method (DTM) was applied to the micro-polar flow in a porous channel with mass injection. Approximate solutions of the governing system of nonlinear ordinary differential equations were calculated in the form of DTM series with easily computable terms. The validity of the series solutions were verified by comparison with numerical results obtained using a fourth order Runge–Kutta method. The computed DTM velocity profiles are shown and the influence of Reynolds number on the velocity component in x-direction is discussed.
Keywords: differential transform method; micro-polar flow; porous channel; system of nonlinear ordinary differential equations